Effectiveness and safety of Shengxuening for treatment of renal anemia: a comprehensive systematic review and meta-analysis - Zheng, Li; Gu, Xiaotong; Liu, Ming; Fu, Changhai; Wang, Yan (Frontiers in Pharmacology, 2025)
AimWe aimed to evaluate the efficacy and safety of Shengxuening (SXN) in treating renal anemia by systematic review and meta-analysis.MethodsPubMed, Embase, the Cochrane Library, the ClinicalTrials.gov, SinoMed, the China Knowledge Network, the Wanfang Data Knowledge Service Platform and Technology Journal Database were searched from inception to September 2024 randomized controlled trials (RCTs) that compared SXN and other drugs or placebo in treating renal anemia. We used the Cochrane Bias Risk Tool to evaluate the risk of bias of all included RCTs, and used the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) to evaluate the certainty of the evidence.Results31 RCTs involving 2,372 patients were included. The efficiency of SXN was superior than the control group (included placebo group, other drugs group) in improving hemoglobin (compared with placebo: MD: 7.15 g/L, 95% CI: 5.68–8.62, P < 0.001, GRADE: high; compared with other drugs: MD: 6.49 g/L, 95% CI: 3.50–9.47, P < 0.001, GRADE: very low), serum ferritin (MD: 57.53 ng/mL, 95% CI: 29.70–85.36, P < 0.001, GRADE: moderate; MD: 28.96 ng/mL, 95% CI: 1.88–56.04, P = 0.04, GRADE: moderate) and transferrin saturation level (MD: 7.00%, 95% CI: 3.40–10.60, P = 0.0001, GRADE: moderate; MD: 3.64%, 95% CI: 1.41–5.88, P = 0.001, GRADE: moderate). Besides, the efficiency of SXN combined with other drugs was superior than other drugs group in improving hemoglobin (MD: 11.95 g/L, 95% CI: 6.19–17.71, P < 0.001, GRADE: moderate), serum ferritin (MD: 53.43 ng/mL, 95% CI: 20.65–86.21, P = 0.001, GRADE: moderate) and transferrin saturation level (MD: 5.91%, 95% CI: 3.72–8.10, P < 0.001, GRADE: moderate). Additionally, the incidence of adverse drug reactions (ADRs) in the SXN group was lower than that in other drugs treatment group (OR: 0.20, 95%CI: 0.12–0.33, P < 0.00001).ConclusionThe efficacy of SXN in treating renal anemia is convincing. Compared with other drugs, SXN is comparable or even better in treating renal anemia. Additionally, the safety of SXN is also relatively high.